Augercast Piles - History And Advancements - Larry Rayburn (Deep Foundations Institute, 2005)
Augercast piles evolved in the late forties from the process of pressure grouting open holes backfilled with stone. In 1956, a patent was issued for a cast in situ pile by pumping high pressure grout through hollow-stem, continuous flight auger as the auger is gradually withdrawn from the ground. The patent rights expired in 1973 and the use of auger-cast piles greatly expanded with most large deep foundation contractors now installing augercast piles. At one time augercast piles had a bad reputation, partly because of not having a blow count to give some engineers a confidence factor and there were some quality issues. Over the years the quality issues have been eliminated and I am sure the augercast is the most installed pile in private industry and is now being used by some State Agencies.